Noninvasive study of coronary microcirculation response to a cold pressor test. (7th January 2015) - Pham, Isabelle; Nguyen, Minh‐Tuan; Valensi, Paul; Rousseau, Hélène; Nitenberg, Alain; Vicaut, Eric; Cosson, Emmanuel
Abstract Background The aims of this study were to noninvasively (i) assess the coronary microcirculation changes in response to a cold pressor test (CPT) in control subjects, nondiabetic obese patients and patients with type 2 diabetes and (ii) investigate the response of the coronary microcirculation in patients with diabetes according to the presence or the absence of silent myocardial ischaemia (SMI), asymptomatic coronary stenosis (CS) and left ventricle hypertrophy (LVH). Methods The mean left anterior descending coronary flow velocity (mCFV) was measured using transthoracic Doppler before and after a CPT in 16 control subjects, 11 obese and 66 asymptomatic diabetic patients with a high cardiovascular risk. Patients with diabetes were screened for SMI using stress myocardial scintigraphy and/or echocardiography. A coronary angiography was performed in those with SMI. Results At baseline, pressure–rate product (PRP) was correlated with mCFV (r = 0·23; P < 0·05) and left ventricle mass (r = 0·26; P < 0·05) in the whole population. Changes in PRP and mCFV during CPT were correlated with controls (r = 0·58, P < 0·05), obese (r = 0·75, P < 0·01) and diabetic patients without CS (r = 0·56, P < 0·0001) or without LVH (r = 0·63, P < 0·05) but not in diabetic patients with CS or with LVH. In patients with diabetes, SMI was associated with mCFV changes, independent of other parameters (P < 0·05). Conclusion Transthoracic coronary Doppler allows noninvasive study of changes in the coronary microcirculation during CPT. In asymptomatic patients with type 2 diabetes, this method showed that SMI was associated with mCFV changes during CPT and the presence of CS or LVH was associated with a mismatch between coronary microcirculation and myocardial oxygen demand.